The Influence Of Service Quality, Customer Relationship Management (CRM) And Brand Image On Customer Loyalty With Customer Satisfaction As An Intervening Variable - Ali Imron; Rizka Ariyanti (International Conference On Digital Advanced Tourism Management And Technology, 2023)
The aim of this research is to determine and analyze the influence of Service Quality, Customer Relationship Management (CRM) and Brand Image on Customer Loyalty with Customer Satisfaction as an intervening variable. This research uses purposive sampling with a sample of 100 respondents. This research testing uses quantitative methods. The validity test results of all question items are valid because the value of rcount > rtable. The reliability test results of all question items are reliable because the Cronbach Alpha value is> 0.60. The results of the classical assumption test all variables meet the classical assumption criteria. The results of multiple linear regression analysis in this research obtained b1 = 0.133 which shows the positive influence of the Service Quality variable (X1) on customer loyalty (Y). Meanwhile b2 = 0.182 shows the positive influence of CRM variables (X2) on Customer Loyalty (Y). Lastly, b3 = 0.252 shows the positive influence of the Brand Image variable (X3) on Customer Loyalty (Y).To test the hypothesis, there is a partially significant influence between Service Quality (X1) on customer loyalty (Y) with a value of tcount > ttable (3.978 > 1.983). CRM (X2) has a partially significant effect on Customer loyalty (Y) with a value of tcount > ttable (2.164 > 1.983). Brand Image (X3) has a partially significant effect on Customer Loyalty (Y) with a value of tcount > ttable (2.335 > 1.986). Customer Satisfaction (Z) mediates the influence of Service Quality (X1) on Customer Loyalty (Y) with a value of tcount > ttable (14.734 > 1.983). Customer Satisfaction (Z) mediates the influence between CRM (X2) on Customer loyalty (Y) with a value of tcount > ttable (10.335>1.983). Customer Satisfaction (Z) mediates the influence of Brand Image (X3) on Customer Loyalty (Y) with a value of tcount > ttable (10.258 > 1.983). Customer Satisfaction (Z) has a partially significant effect on Customer Loyalty (Y) with a value of tcount > ttable (3.513 > 1.983).